2019
DOI: 10.32866/001c.11210
|View full text |Cite
|
Sign up to set email alerts
|

Sunday Drivers, or Too Fast and Too Furious?

Abstract: The recent influx of electric scooters (e-scooters) has left cities scrambling to answer how to best to regulate them. To help inform policymaking, we studied escooter riding behavior through observations of speed and rider distractions.Observations show e-scooter riders travel faster on streets and slower on sidewalks and slightly slower than cyclists on streets. Additionally, few e-scooter riders wear helmets, and some may be distracted by headphones but not by handling cellphones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…As for helmet use, we did not observe a single shared e-scooter user wearing a helmet during the 12.5 hours of observation in Berlin. This finding of 0% helmet use, shared with other previous studies addressing e-scooter riders' safety in Germany (Störmann et al, 2020) is critically smaller than findings from other countries (Arellano & Fang, 2019;Haworth, Schramm, & Twisk, 2021;Todd et al, 2019). The non-use of helmets by shared escooter users in Germany is especially alarming in light of findings of frequent head injuries of hospitalized escooter riders (Aizpuru et al, 2019;Trivedi et al, 2019).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…As for helmet use, we did not observe a single shared e-scooter user wearing a helmet during the 12.5 hours of observation in Berlin. This finding of 0% helmet use, shared with other previous studies addressing e-scooter riders' safety in Germany (Störmann et al, 2020) is critically smaller than findings from other countries (Arellano & Fang, 2019;Haworth, Schramm, & Twisk, 2021;Todd et al, 2019). The non-use of helmets by shared escooter users in Germany is especially alarming in light of findings of frequent head injuries of hospitalized escooter riders (Aizpuru et al, 2019;Trivedi et al, 2019).…”
Section: Discussioncontrasting
confidence: 45%
“…The authors concluded that helmet use is related to the type of e-scooter, i.e., if a private of rental/shared escooter is used (Haworth & Schramm, 2019). Other studies have found even lower helmet use for shared escooters, e.g., between 2% and 10.9% in California, U.S.A. (Arellano & Fang, 2019;Todd, Krauss, Zimmermann, & Dunning, 2019) and 0.4% in Berlin, Germany (Siebert et al, 2020). While helmet use is not mandatory in Germany, e-scooter providers advise for helmet use in their apps and directly with pictograms on e-scooters (Fig.…”
Section: Helmet Usementioning
confidence: 97%
“…Such actions suggest there is a belief that shared e‐scooters can substitute BSS in urban areas to some extent. The potential similarities between e‐scootering and cycling have been noted (Arellano & Fang, 2019; McKenzie, 2019). Although e‐scooter schemes might to appeal to a similar demographic as BSS (McKenzie, 2019).…”
Section: Introductionmentioning
confidence: 80%
“…While such analysis rightly points out that the dockless schemes are more equitable that previous BSS in terms of social patterning of users, the lower rate of usage still perpetuates, rather than addresses, inequities. Absolute usage rates may also mask differences in the ways in which modes of transport are used by different groups; Arellano and Fang (2019) note that men ride e‐scooters faster than women, and NZ figures show that although similar proportions of men and women drive, men drive much more (Ministry of Transport, 2019). Rather than claiming equity or inclusiveness because of having more equitable usage than the existing situation transport policy should focus on developing transport innovations that primarily meet the needs of those who are transport deprived in order to address existing inequities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation